2021
DOI: 10.1021/acsanm.1c03093
|View full text |Cite
|
Sign up to set email alerts
|

Fe3C/Carbon-Coated Fe3O4 Core–Shell Nanoparticles as Recyclable Catalysts for Ciprofloxacin Degradation in Water

Abstract: On using magnetic Fe3O4 as the core of nitrogen-doped carbon (NC) matrix composite Fe3C (Fe3C/Fe3O4@NC), it not only shows good peroxide-like and oxidase-like properties but also has excellent Fenton-like degradability. Based on the Fenton-like properties of the core–shell nanocomposites, ciprofloxacin can be degraded by activated peroxo monosulfate. The magnetic core is easy to recover, and the shell has good catalytic performance. The degradation rate using Fe3C/Fe3O4@NC as the catalyst was 7.3 and 2.9 times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Organic contaminants of different industries, like dyes, pharmaceuticals, agro-industries, personal care products, etc., cause irreversible harm to the environment and ecosystem through bioaccumulation and transmission through the food chain. 10,11 These recalcitrant contaminants are difficult to degrade by conventional techniques, such as advanced oxidation, Fenton process, etc. 11 Thus, a photocatalyst having high catalytic activity is a suitable option for their degradation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic contaminants of different industries, like dyes, pharmaceuticals, agro-industries, personal care products, etc., cause irreversible harm to the environment and ecosystem through bioaccumulation and transmission through the food chain. 10,11 These recalcitrant contaminants are difficult to degrade by conventional techniques, such as advanced oxidation, Fenton process, etc. 11 Thus, a photocatalyst having high catalytic activity is a suitable option for their degradation.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 These recalcitrant contaminants are difficult to degrade by conventional techniques, such as advanced oxidation, Fenton process, etc. 11 Thus, a photocatalyst having high catalytic activity is a suitable option for their degradation. 12,13 Borophene is the lightest 2D anisotropic Dirac material of single-atom boron.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have been reported where pure and a combination of various catalysts were prepared by different methods such as by a Mn-doped Fe-based metal–organic framework (MOF), BiOI/MIL-53­(Fe) Z-scheme heterojunction (named BMFe) catalysts, nano-FeO x /CN core–shell-structured catalyst, Fe/MIL-100­(Cr) and Fe/MIL-101­(Cr) catalysts, sulfidated Fe 3 S 4 @β-FeOOH, core–shell-structured Mn 3 O 4 @SiO 2 NB, magnetic Fe 3 O 4 as the core of a nitrogen-doped carbon (NC) matrix composite Fe 3 C (Fe 3 C/Fe 3 O 4 @NC), nitrogen-doped carbon nanotube-encapsulated Fe 3 C (Fe 3 C@NCNT), Fe cores (Fe@C) derived from CDM (catalytic decomposition of methane) particles, Fe 3 O 4 @β-CD/g-C 3 N 4 β-cyclodextrin/graphitic carbon nitride, Fe/Cu/zeolite catalysts, and X-type zeolite molecular sieve catalysts modified with copper (Cu-X) catalysts …”
Section: Introductionmentioning
confidence: 99%
“…20 Hence, heterogeneous Fenton's oxidation processes are a potential way to clean industrially polluted water even in a dark environment. 21 Several recent studies have been reported where pure and a combination of various catalysts were prepared by different methods such as by a Mn-doped Fe-based metal−organic framework (MOF), 22 BiOI/MIL-53(Fe) Z-scheme heterojunction (named BMFe) catalysts, 23 nano-FeO x /CN core− shell-structured catalyst, 23 Fe/MIL-100(Cr) and Fe/MIL-101(Cr) catalysts, 24 sulfidated Fe 3 S 4 @β-FeOOH, 25 core− shell-structured Mn 3 O 4 @SiO 2 NB, 26 magnetic Fe 3 O 4 as the core of a nitrogen-doped carbon (NC) matrix composite Fe 3 C (Fe 3 C/Fe 3 O 4 @NC), 27 nitrogen-doped carbon nanotube-encapsulated Fe 3 C (Fe 3 C@NCNT), 28 Fe cores (Fe@C) derived from CDM (catalytic decomposition of methane) particles, 29 Fe 3 O 4 @β-CD/g-C 3 N 4 β-cyclodextrin/graphitic carbon nitride, 30 Fe/Cu/zeolite catalysts, 31 and X-type zeolite molecular sieve catalysts modified with copper (Cu-X) catalysts. 32 A recent report from Yang et al showed that the nanocomposites containing FeS as a catalyst and MoS 2 as a co-catalyst creates a strong contact between the two components and yields a significant number of Mo 6+ sites and sulfur vacancies, which contribute to the enhanced degradation rate by accelerating Fe 3+ /Fe 2+ cycling.…”
Section: Introductionmentioning
confidence: 99%